2006
DOI: 10.1300/j021v26n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Geriatrics Interdisciplinary Experience on Learners' Knowledge and Attitudes

Abstract: This study examines the impact of an interdisciplinary training program on knowledge and attitudes of learners from four health care programs: medicine, pharmacy, social work, and nursing. Sixty-two learners participated in a 4-day educational program (one day each week for 4 weeks) focusing on interdisciplinary geriatric care. After completing the program, learner scores improved on a knowledge test and two attitudinal subscales, and they reported a positive training experience. A short-term interdisciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Although both nursing and nonnursing students exhibited increases in positive attitudes and feelings over time which is consistent with the literature, [11,13,40] no significant interaction effect of time by group was shown. The improvement of positive attitudes in both groups over time may be attributed to the Hawthorne effect, a change in behavior simply due to being studied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although both nursing and nonnursing students exhibited increases in positive attitudes and feelings over time which is consistent with the literature, [11,13,40] no significant interaction effect of time by group was shown. The improvement of positive attitudes in both groups over time may be attributed to the Hawthorne effect, a change in behavior simply due to being studied.…”
Section: Discussionsupporting
confidence: 91%
“…[12] Based on the Triadic Model, education and experience may impact the attitudes of young adults, but the effect of education in attitudes has not been well studied. In some cases, college students (nursing, medicine, pharmacy, and social work), who took a gerontology course improved their knowledge and developed positive attitudes toward aging, [13,14] and had reduced negative attitudes toward aging. [15,16] However, other studies concluded that educational experiences did not change nursing students' attitudes toward aging.…”
Section: Introductionmentioning
confidence: 99%
“…Service learning promotes learning of new skills and application of those skills in real situations that benefit not only the student, but also the community (Weinreich, 2003). Service learning in gerontology courses leads to students having more positive attitudes toward older adults (Fitzgerald et al, 2006;Krout et al, 2010) and has been shown to improve gerontological competencies (Dauenhauer, Steitz, Aponte, & Fromm Faria, 2010;. Likewise, older adults report developing an increased understanding of the younger generation, valued sharing their life experiences, and enjoying the social contact they had with college students (Underwood & Dorfman, 2006).…”
Section: Interprofessional Education Gerontology and Service Learningmentioning
confidence: 99%
“…Prior research has demonstrated that college students in health-related majors who had taken a gerontology course improved their knowledge about older adults, developed positive attitudes toward aging, [8,9] and reduced their negative attitudes toward older adults. [10,11] Yet other studies found that educational experience did not change students' attitudes toward aging.…”
Section: Introductionmentioning
confidence: 99%